Comprehensive insect physiology, biochemistry and pharmacology. - Kerkut, G. A.; Gilbert, Lawrence I. (Lawrence Irwin), 1929-2017 (Comprehensive insect physiology, biochemistry and pharmacology, 1985)
In this volume, seven of the chapters deal with feeding and diet, which is reasonable since insects consume an estimated l5-20% of all the world's planted crops. Many insects even have a specialized larval feeding stage that usually occupies a different ecological niche to the adult and so does not compete for the adult's food stock. Other chapters describe the means by which insects maintain their water balance, nitrogen balance and temperature balance under a range of conditions. These involve regulation by hormonal and behavioural systems that are also described here. The l4 chapters ar.